특수교육대상영유아 가족지원 프로그램에 대한 장애아전문어린이집 부모와 교사의 인식 - 김수현(Kim, Su Hyun); 이병인(Lee, Byoung-In) (특수교육논총, 2020)
연구 목적: 본 연구는 장애아전문어린이집에 재원 중인 특수교육대상영유아의 부모와 교사를 대상으로 가족지원 프로그램에 대한 배경 변인에 따른 인식과 집단 간의 차이를 알아보고자 하였다. 연구 방법: 연구 대상은 경기도 지역의 장애아전문어린이집에 재원 중인 특수교육대상영유아 부모 253명과 같은 원에 근무하고 있는 영유아 담당 교사 167명을 대상으로 하였다. 설문문항은 대상자의 기초사항과 가족지원 프로그램에 대한 인식을 알아보는 문항으로 구성하였다. 설문 조사를 통해 불성실하게 표기하거나 중복 표기된 설문지를 제외하고 부모용 197부와 교사용 164부가 최종 분석 자료로 사용하였다. 연구 결과: 연구 결과를 요약하면 첫째, 특수교육대상영유아 가족지원 프로그램에 대해서 부모와 교사의 전반적인 인식은 모두 높았다. 둘째, 부모의 인식은 월 평균 소득과 직업에 따라 차이가 있었으며 교사의 인식은 학력에 따라 차이가 있었다. 셋째, 가족지원 프로그램에 대한 부모와 교사의 인식의 차이는 부모참여 지원 프로그램, 부모교육 프로그램, 가족 상담지원 프로그램, 지역사회 연계 프로그램에서 유의한 차이가 있는 것으로 나타났다. 결론: 본 연구는 장애아전문어린이집에서 부모와 교사의 가족지원 프로그램에 대한 배경 변인에 따른 인식과 집단 간의 차이를 알아봄으로써 효과적인 장애아전문어린이집의 가족지원 프로그램의 개발 및 적용을 위한 기초 자료로 사용될 수 있을 것으로 기대된다. Purpose: The purpose of this study was to investigate the perceptions of parents and teachers of young children with special needs on the family support programs according to the background variables and the difference of perceptions between two groups whose children are enrolled in childcare centers. Method: The subjects of the study were 253 parents and 167 teachers of childcare centers for young children with disabilities in Gyeonggi-do. The questionnaire consisted of the basic information of the subjects and the perceptions of the family support programs. Among the collected data, 197 parents and 164 teachers were finally used as the final analysis data, except for the questionnaires which were not recorded appropriately or duplicated. Results: The results of this study are as follows. First, the parents and teachers' perception of the family support programs for young children with special needs was relatively high. Second, parents' perceptions differed according to their average monthly income and occupation and teachers' perceptions differed according to their educational background. Third, differences in parents and teachers' perceptions of family support programs were significantly different between parent participation support programs, parent education programs, family counseling support programs and community allied programs. Conclusion: This study is expected to be applied as basic data for the development and application of the family support programs for young children with special needs by identifying differences in parents and teachers’ perceptions of family support programs and the perceptions based on background variables of parents and teachers. KCI Citation Count: 6